THE EFFECT OF PROVIDING AB MIX GROWTH REGULATORY SUBSTANCES AND NPK FERTILIZER ON THE GROWTH AND PRODUCTION OF CHERRY TOMATO (Solanum Lycopersicum Mill) PLANT WITH A HYDROPONIC CULTIVATION SYSTEM: PENGARUH PEMBERIAN ZAT PENGATUR TUMBUH AB MIX DAN PUPUK NPK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN TOMAT CERI (Solanum Lycopersicum Mill) DENGAN SISTEM BUDIDAYA HIDROPONIK - Zebua, Marfengki (UPMI Proceeding Series, 2023)
Cherry tomato (Solanum lycopersicum Mill) continues to increase production in line with high demand. High quality production demands method development and one solution is to use the Hydroponic System Wick. This method requires a study with the aim of knowing the effect of the treatment given and the best treatment for recommendations for farmers and practitioners. The research design was based on completely randomized design with two treatment factors, namely the concentration of AB mix nutrients and NPK fertilizer. The NPK concentration factor (N) consisted of 3 treatments namely AB1 0 ppm, AB2 1300 ppm, AB3 1600 ppm and the NPK fertilizer concentration factor (N) which consisted of 3 treatments namely N1 0 ppm (0 gr/l), N2 750 ppm ( 0.75 gr/l), N3 1500 ppm (1.5 gr/l). This research was conducted randomly with 3 repetitions, so that 27 experimental units were obtained by observing stem diameter, plant height, number of flowers, number of leaves, fresh fruit production per plot, fresh fruit production per plot, number of fruit per plot, number of fruit per sample planting. Treatment of AB mix nutrient concentration and NPK fertilizer, the interaction of the two had a significant effect on the research parameters. The best results in various treatments were found in the concentration of the AB MIX nutrient solution with a nutrient concentration of 1300 ppm which can be a recommendation in the cultivation of cherry tomatoes with a hydroponic wick system.